(untitled) (Scientific Journal for Publishing in Health Research and Technology, 2025)
This study aimed to provide a comprehensive critical analysis of diagnostic tools and developed intervention mechanisms for addressing Advanced Mathematics Learning Difficulties (AMLD), encompassing areas such as abstract algebra, calculus, and spatial geometry, within a timeframe spanning from 2000 to 2023. The study adopted a Systematic Critical Review methodology in accordance with the PRISMA protocol, analyzing 127 studies extracted from reputable academic databases. Pivotal results confirmed that diagnostic efficacy is contingent upon adopting a multidimensional integrative framework that includes cognitive, affective, and meta-cognitive aspects. Although cognitive assessment tools, such as the Algebra Thinking Test (ATT), demonstrated moderate efficacy (effect size d = 0.62), intervention strategies based on multiple representations and meta-cognitive training recorded the highest levels of effectiveness, with effect sizes reaching d = 0.79 and d = 0.75, respectively. The study also revealed three critical research challenges: firstly, a severe shortage of culturally calibrated assessment tools, with only 15% being valid for use in Arabic contexts; secondly, weak effective utilization of advanced technology in diagnosis (with only 12% employing artificial intelligence techniques); and thirdly, a systematic omission of diagnosing spatial geometry difficulties in approximately 73% of the published research.